On the identity of Dichotrachelus maculosus Fairmaire and D. sabaudus Fairmaire (Coleoptera: Curculionidae: Cyclominae) - Meregalli, Massimo; Perrin, Hélène (Zootaxa, 2012)
During the compilation of the Catalogue of the Palaearctic Coleoptera: Curculionidae: Cyclominae by the first author, particular attention was given to the correct identification of a few early names of uncertain attribution within Dichotrachelus Stierlin, 1853. Early description and geographical distribution suggested that two of these names could be the senior synonyms of commonly used names for species of the Western Alps. Both these names have been placed in synonymy with other species, sometimes doubtfully and not respecting priority.